Beyond successful hemostasis: CT findings and organ failure predict postoperative death in patients suffering from post-pancreatoduodenectomy hemorrhage. Issue 2 (February 2023) - Yang, Jie; Chen, Yonghua; Liu, Xubao; Zheng, Zhenjiang; Wang, Xing; Li, Yichen; Tan, Chunlu
Abstract: Background: To predict postoperative death even after successful hemostasis in patients with post pancreatoduodenectomy pancreatic fistula-associated hemorrhage (PPFH). Methods: Patients who underwent pancreatoduodenectomy (PD) between September 2011 and August 2020 were identified. PPFH patients were enrolled in this retrospective case–control study and divided into the Cured and Death groups. Perioperative variables were analyzed, especially the characteristics of PPFH and CT image findings. Results: Among the 2732 consecutive pancreaticoduodenectomies, 63 patients (2.3%) were confirmed to have PPFH. The mortality rate of patients following PPFH was 50.8% (32/63). After univariate and multivariate analysis, organ failure 24 h before initial hemorrhage ( P = 0.039, OR = 11.53, 95% CI: 1.14–117.00), CT imaging findings of the operative area bubble sign (P = 0.021, OR = 5.15, 95% CI: 1.28–20.79) and PJ dehiscence (P = 0.016, OR = 8.95, 95% CI: 1.50–53.38) were remained as significant predictive factors of postoperative death for PPFH patients. Conclusions: Patients following PPFH showed a high mortality rate. Organ failure and CT evidence of pancreaticojejunostomy (PJ) dehiscence and operative area bubble signs before initial hemorrhage may allow early prediction of postoperative death in PPFH patients.